Moving Liquids with Sound: The Physics of Acoustic Droplet Ejection for Robust Laboratory Automation in Life Sciences. (February 2016) - Hadimioglu, Babur; Stearns, Richard; Ellson, Richard
Liquid handling instruments for life science applications based on droplet formation with focused acoustic energy or acoustic droplet ejection (ADE) were introduced commercially more than a decade ago. While the idea of "moving liquids with sound" was known in the 20th century, the development of precise methods for acoustic dispensing to aliquot life science materials in the laboratory began in earnest in the 21st century with the adaptation of the controlled "drop on demand" acoustic transfer of droplets from high-density microplates for high-throughput screening (HTS) applications. Robust ADE implementations for life science applications achieve excellent accuracy and precision by using acoustics first to sense the liquid characteristics relevant for its transfer, and then to actuate transfer of the liquid with customized application of sound energy to the given well and well fluid in the microplate. This article provides an overview of the physics behind ADE and its central role in both acoustical and rheological aspects of robust implementation of ADE in the life science laboratory and its broad range of ejectable materials.